2017
DOI: 10.17576/3l-2017-2303-06
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Trainees’ Perspectives of Teaching Graphic Novels to ESL Primary Schoolers

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Following the articles' analysis, lack of visual literacy among students and teachers was discovered to be the most frequently mentioned challenge of teaching graphic novels in English classes (Masood & Iranmanesh, 2012;Cimermanova, 2014;Yusof et al, 2017;Yusof et al, 2020). According to Felten (2008), visual literacy is described as the ability to identify, comprehend, and make use of the distinctive syntax and semantics of various visual forms.…”
Section: Lack Of Visual Literacymentioning
confidence: 99%
See 3 more Smart Citations
“…Following the articles' analysis, lack of visual literacy among students and teachers was discovered to be the most frequently mentioned challenge of teaching graphic novels in English classes (Masood & Iranmanesh, 2012;Cimermanova, 2014;Yusof et al, 2017;Yusof et al, 2020). According to Felten (2008), visual literacy is described as the ability to identify, comprehend, and make use of the distinctive syntax and semantics of various visual forms.…”
Section: Lack Of Visual Literacymentioning
confidence: 99%
“…On the other hand, a study from Yusof et al (2017), found that students were more preoccupied with the images and have failed to read the words in speech balloons while reading the graphic novels in class due to a lack of visual literacy and multiliteracies. This eventually caused them to comprehend the content incorrectly and their input became unclear.…”
Section: Lack Of Visual Literacymentioning
confidence: 99%
See 2 more Smart Citations
“…questions (Dreyer, 2016;Hwang & Embi, 2007;Yusof, Lazim, & Salehuddin, 2017). Open-ended questions can be used to allow students to predict outcomes, make comparisons and draw conclusions.…”
Section:  Increases Motivationmentioning
confidence: 99%